Engineering CXCL12 Biomimetic Decoy‐Integrated Versatile Immunosuppressive Nanoparticle for Ischemic Stroke Therapy with Management of Overactivated Brain Immune Microenvironment (Small Methods 1/2022). Issue 1 (18th January 2022) - Shi, Jinjin; Yang, Yue; Yin, Na; Liu, Changhua; Zhao, Yuzhen; Cheng, Hui; Zhou, Tonghai; Zhang, Zhenzhong; Zhang, Kaixiang
Abstract : Back Cover In article number 2101158, Shi, Yang, and co‐workers report an engineering CXCL12 biomimetic decoy‐integrated versatile immunosuppressive nanoparticle (VIN). VIN integrates inflammation tropism, peripherally inflammatory cells filtrate, brain‐resident activated microglia polarization, as well as ROS scavenging. As a result, the VIN can promote outstanding therapeutic effects on ameliorating the mortality, reducing the infarct volume and protecting neurons post‐stroke.